Impact of turbulent mixing on isoprene chemistry. Issue 14 (22nd July 2016) - Kim, S.‐W.; Barth, M. C.; Trainer, M.
Abstract: Isoprene, a volatile organic compound that is mainly emitted from trees, rapidly reacts with hydroxyl radical (OH) during daytime and subsequently forms ozone and aerosols in the troposphere. The isoprene‐OH reaction can be affected by the interplay between chemistry and mixing because the two processes occur at a similar time scale. We investigate the impact of turbulent mixing on isoprene‐OH reactivity with large eddy simulations (LES) coupled with comprehensive chemistry. Our results show that the covariance of isoprene and OH causes 20% decrease to 10% increase of the horizontal average reaction rate, depending on nitrogen oxides (NO x = NO + NO2 ) abundances, compared to the rate that neglects the covariance. This wide range of effects on reaction rates is caused by the primary production and loss reactions of OH in each NO x regime. Our research promotes the use of LES for better understanding the role of turbulence in isoprene‐OH reaction and parameterizations in large‐scale models. Key Points: LES with comprehensive chemistry is used for study of isoprene chemistry Turbulence can decrease or increase the isoprene‐OH reaction rate NOx levels influence the range of the effects of turbulence on the reactivity